The pitfalls of exaggeration: molecular and morphological evidence suggests Kaliana is a synonym of Mesabolivar (Araneae: Pholcidae) - Astrin, Jonas J.; Misof, Bernhard; Huber, Bernhard A. (Zootaxa, 2007)
When the Venezuelan genus Kaliana Huber, 2000 was described, it was based on a single male specimen that was morphologically unique among pholcid spiders, especially in its extremely exaggerated male genitalia. The morphology of the recently discovered female suggests a close relationship with Mesabolivar González-Sponga, 1998. Using molecular sequences (mitochondrial CO1, 16S, and nuclear 28S) of Kaliana yuruani Huber, 2000 and 53 other pholcid taxa (152 sequences, 19 of them sequenced in this study) in a Bayesian and a maximum parsimony approach, we show that Kaliana is not sister group of, but nested within the species-rich South American genus Mesabolivar. Therefore, we argue that Kaliana is a junior synonym of Mesabolivar (Mesabolivar yuruani, n. comb.). Complementing previous studies on pholcid phylogeny, we also present evidence for a close relationship between Mesabolivar and Carapoia, support the synonymy of Anomalaia and Metagonia with molecular data, support the monophyly of 'ninetines' and question the recently postulated position of Priscula as nested within the New World clade.